Moderasi Beragama Sufi: Sikap dan Pemikiran Imam al-Qusyairi - Damanik, Deniansyah (UIN Sunan Kalijaga Yogyakarta, 2021)
Religions moderation is necessary to be applied nowadays, because many people do not understand the outcome of having the moderate perspective and behaviour. The moderate behaviour and perspective is also advocated by sufis. It is the more interesting because sufis tend to commence phisical and spiritual rituals. In this article, I elaborate on the attitude and the view of religious moderation of one of the renowned sufis, namely Imām al-Qusyairī through his work Risālah al-Qusyairiyah. The attitude and the view of religious moderation of Imām al-Qusyairī is not limited to tasāmuḥ (tolerant), tawassuṭ (middle ground), and tawāzun (balanced), but more than that.